CYBERACTIVISM SEBAGAI BUDAYA POPULER: ANALISIS WACANA HASHTAG #PERCUMALAPORPOLISI DI TWITTER - Latief, Rahmawati; Bahar, Nurfadhilah (Jurnal Dakwah Tabligh, 2022)
The effectiveness of Twitter in forming a community has an impact on the movement of activists on social media or what is called cyber activism. Moreover, it is coupled with the trending topic feature with the use of hash marks or hashtags (#) which makes it easy for users to find out the most discussed topics, both on a national and global. The #PercumaLaporPolisi tweet is one of the hashtags on Twitter that became a trending topic on October 7, 2021, which became the source of research data. This study aims to interpret public opinion as a social movement in a discourse of the tweet #PercumaLaporPolisi which is a trending topic on Twitter. This study uses the discourse analysis method of Teun Adrianus Van Dijk, namely the macrostructure, superstructure, and microstructure. The results showed that the most prominent theme was the negative image of the police by netizens with the style of sarcasm and satire. The pattern of netizen opinion schemes follows the development of this case issue every day. The uploader of the hashtag #PercumaLaporPolisi has the intention of making cases viral as a warning to the police to make improvements. Uploads that get more responses from netizens will become more popular, thus encouraging the authorities to take action.